Activated Schwann cells in pancreatic cancer are linked to analgesia via suppression of spinal astroglia and microglia. Issue 6 (13th January 2016) - Demir, Ihsan Ekin; Tieftrunk, Elke; Schorn, Stephan; Saricaoglu, Ömer Cemil; Pfitzinger, Paulo L; Teller, Steffen; Wang, Kun; Waldbaur, Christine; Kurkowski, Magdalena U; Wörmann, Sonja Maria; Shaw, Victoria E; Kehl, Timo; et al.
Abstract : Objective: The impact of glia cells during GI carcinogenesis and in cancer pain is unknown. Here, we demonstrate a novel mechanism how Schwann cells (SCs) become activated in the pancreatic cancer (PCa) microenvironment and influence spinal activity and pain sensation. Design: Human SCs were exposed to hypoxia, to pancreatic cancer cells (PCCs) and/or to T-lymphocytes. Both SC and intrapancreatic nerves of patients with PCa with known pain severity were assessed for glial intermediate filament and hypoxia marker expression, proliferation and for transcriptional alterations of pain-related targets. In conditional PCa mouse models with selective in vivo blockade of interleukin (IL)-6 signalling (Ptf1a-Cre;LSL-Kras G12D /KC interbred with IL6 −/− or sgp130 tg mice), SC reactivity, abdominal mechanosensitivity and spinal glial/neuronal activity were quantified. Results: Tumour hypoxia, PCC and/or T-lymphocytes activated SC via IL-6-signalling in vitro. Blockade of the IL-6-signalling suppressed SC activation around PCa precursor lesions (pancreatic intraepithelial neoplasia (PanIN)) in KC;IL6 −/− (32.06%±5.25% of PanINs) and KC;sgp130 tg (55.84%±5.51%) mouse models compared with KC mice (78.27%±3.91%). Activated SCs were associated with less pain in human PCa and with decreased abdominal mechanosensitivity in KC mice (von Frey score of KC: 3.9±0.5 vs KC;IL6 −/− mice: 5.9±0.9; and KC;sgp130 tg : 10.21±1.4) parallel to attenuation of spinal astroglial and/or microglial activity. Activated SC exhibited a transcriptomic profile with anti-inflammatory and anti-nociceptive features. Conclusions: Activated SC in PCa recapitulate the hallmarks of 'reactive gliosis' and contribute to analgesia due to suppression of spinal glia. Our findings propose a mechanism for how cancer might remain pain-free via the SC–central glia interplay during cancer progression.